Descriptions of two new species of Neuroterus Hartig from China (Hymenoptera: Cynipidae) - Pujade-Villar, Juli; Wang, Yiping; Liu, Zhiwei; Guo, Rui (Entomologica Fennica, 2016)
Two morphologically unusual new species of Neuroterus Hartig, Neuroterus sculpturatus Pujade-Villar & Wang sp. n. and N. abdominalis Pujade-Villar & Wang sp. n., are described fromChina. Data about galls, distribution and biology of the new species are included. Taxonomic problems concerning some of the Palaearctic Neuroterus species, including the species described here, are also commented.